2016
DOI: 10.1080/09168451.2015.1127135
|View full text |Cite
|
Sign up to set email alerts
|

Production of keto-disaccharides from aldo-disaccharides in subcritical aqueous ethanol

Abstract: Isomerization of disaccharides (maltose, isomaltose, cellobiose, lactose, melibiose, palatinose, sucrose, and trehalose) was investigated in subcritical aqueous ethanol. A marked increase in the isomerization of aldo-disaccharides to keto-disaccharides was noted and their hydrolytic reactions were suppressed with increasing ethanol concentration. Under any study condition, the maximum yield of keto-disaccharides produced from aldo-disaccharides linked by β-glycosidic bond was higher than that produced from ald… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…The aldo‐disaccharides, cellobiose, maltose, lactose, and melibiose, mainly isomerized to their respective corresponding keto‐disaccharides, cellobiulose, maltulose, lactulose, and melibiulose, in high yields with a small amount of monosaccharides produced from the hydrolysis of disaccharides and the mutual isomerizations. In addition, the hydrolysis of the aldo‐disaccharides was suppressed compared to the case in subcritical water . In particular, cellobiulose and maltulose can be produced in ∼ 65 % and 51 % yields, respectively, with high selectivities and total disaccharide contents in the effluent.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…The aldo‐disaccharides, cellobiose, maltose, lactose, and melibiose, mainly isomerized to their respective corresponding keto‐disaccharides, cellobiulose, maltulose, lactulose, and melibiulose, in high yields with a small amount of monosaccharides produced from the hydrolysis of disaccharides and the mutual isomerizations. In addition, the hydrolysis of the aldo‐disaccharides was suppressed compared to the case in subcritical water . In particular, cellobiulose and maltulose can be produced in ∼ 65 % and 51 % yields, respectively, with high selectivities and total disaccharide contents in the effluent.…”
Section: Resultsmentioning
confidence: 54%
“…These results also showed the effects of the type of glycosidic bond and constituent monosaccharides of the aldo‐disaccharides on their isomerizations. The aldo‐disaccharides linked by β ‐glycosidic bonds (cellobiose and lactose) produced the corresponding keto‐disaccharides in higher yields and selectivities than those linked by α ‐glycosidic bonds (maltose and melibiose), which was similar to the case in subcritical aqueous ethanol . However, the effect of the constituent monosaccharides on the aldo‐saccharide isomerization was not detected in subcritical aqueous ethanol.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…GlcA is converted to d-glucuronolactone (GlcL) in subcritical water (Wang et al, 2010). We previously reported that the addition of ethanol to water significantly promotes the isomerization of mono-and disaccharides under subcritical conditions (Gao et al, 2014;2015a;2015b;2015c;2016).…”
Section: Introductionmentioning
confidence: 99%
“…Under subcritical conditions, a mixture of ethanol and water was more effective than water alone for the extraction of phenolic and antioxidative substances from defatted rice bran and rice straw [17,18]. The isomerization of common saccharides to rare ones was promoted by the addition of ethanol to water [19,20]. Although the treatment of chitin in subcritical aqueous ethanol was not examined, similar treatment of GlcNAc and glucosamine should provide basic knowledge on the phenomena that occur during the treatment.…”
Section: Introductionmentioning
confidence: 99%